NASKAH AL-JAWAHIR AL-KHAMSAH SEBAGAI SUMBER RUJUKAN AJARAN TAREKAT SYATTARIYAH DAN PERSEBARAN SALINANNYA - Muhamad Shoheh (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2018)
This paper discusses the context of the written text of alJawahir al-khamsah by Syaikh al-MuhammadAl-Gaus al-Hindi and its relation to a number of other texts which become the source of reference teaching institutes Syattariyah. It also discussed the important position of al-Jawahir al-khamsah text for the followers of the Syattariyah congregation, as well as a general overview of the distribution of copies either in India, Haramayn, and the archipelago. Kitab Al-Jawahir Al-khamsah is a practical book for the followers of Syattariyah congregation the most popular, because it was written based on the author's experience of spiritual exercises tauGt by the teacher, Syaikh Zuhur al-Haji Huduri, for more than 13 years at the top of Mount Janar (Cunar), North India. Kitab al-Jawahir al-Khamsah is a complement of the book of reference Lata'if al-Gaibiyyah and Risalah Syatariyah. So called, because the book of al-Jawahir al-Khamsah contains concepts the idea of founders Syattariyah (Syaikh 'Abdullah al-Syattar and his followers (Syaikh Baha'uddin), but in a more practical form. Syaikh al-Mufammad Al-Gaus called it asa ''jewel